Pengaruh Metode Penyuluhan Kesehatan Terhadap Pengetahuan Tentang Gizi Pada Siswa Sman 1 Nogosari - Afriyanto, Dzul Fahmi; Annisa, Difa (Jurnal Pendidikan Kesehatan (e-Journal), 2024)
Adolescence is a period of human growth and maturity, during this period very unique and sustainable changes occur which will affect health and nutritional status. Insufficient intake between requirements and adequacy will cause nutritional problems, whether in the form of over-nutrition or under-nutrition. So steps are needed to increase knowledge, understanding and awareness about good and correct balanced nutrition. This research aims to determine whether there is an influence in increasing knowledge about balanced nutrition in adolescents before and after being given health education interventions. This research is a type of experimental research in the form of Pre-Experimental Designs. The research design is One Group Pretest-Posttest Design. The research population was 36 students of SMA Negeri 1 Nogosari, Boyolali Regency. Based on the results of the Wilcoxon sign rank test, a p-value of 0.000 was obtained, where the p value <0.05, so Ha was accepted and Ho was rejected, so it can be concluded that there is a significant difference between before (pretest) and after (posttest) it was carried out. counseling methods about balanced nutrition.